O ensino da estatística descritiva para o tratamento da informação no ensino médio - Miléo, Maria Tereza Rodrigues (2017)
In our globalized society the student is constantly subjected to information that needs to be decoded, interpreted and understood. Thus, the understanding of the process of information processing becomes essential, making descriptive statistics assume its key role in the interpretation and analysis of data. In this sense, the main objective of the present work is to address the contributions and difficulties of a methodology of descriptive statistics teaching by means of technology - specifically the spreadsheet - proposed and applied in a class of high school students of the State School Dr. Almir Gabriel, located in the city of Oriximiná PA. In the line of research "Technologies of information, communication and interaction applied to the teaching of Sciences and Mathematics," was based on David Ausubel's Theory of Meaningful Learning (TAS) and used a didactic sequence based on the concept of Unit of Potentially Significant Teaching (LIFO), as recommended by Marco A. Moreira. This was structured in thirteen meetings, having for contextualization the Culture Paraense. Also, in this study, bibliographic and field research and participant observation were carried out. Regarding the approach, emphasis was placed on a methodology of mixed research, that is, quantitative and qualitative research. The following steps were taken for its accomplishment: bibliographical survey; school and class definition; construction of the educational product; application of the educational product; data analysis; and interpretation of the data collected. Therefore, in this context, it was understood that the research reached the proposed objectives by presenting a study that identified information literacy skills (decoding, comprehension, interpretation and retention) that statistical teaching can arouse in the student considering their participation in some stages of the statistical method. It was evidenced that the insertion of a methodology of teaching using technology allowed to enhance the teaching and learning process of descriptive statistics. And that, based on the findings of this study, the methodology of applied teaching contributed to the meaningful learning of the students of the second grade of the school researched. Finally, it is emphasized that this dissertation is accompanied by an educational product that brings together the material used in the meetings and the didactic sequence developed.